Cree encephalitis is allelic with Aicardi-Goutiéres syndrome: implications for the pathogenesis of disorders of interferon alpha metabolism. Issue 3 (1st March 2003) - Crow, Y J; Black, D N; Ali, M; Bond, J; Jackson, A P; Lefson, M; Michaud, J; Roberts, E; Stephenson, J B P; Woods, C G; Lebon, P
Abstract : Aicardi-Goutiéres syndrome (AGS) is an early onset, progressive encephalopathy characterised by calcification of the basal ganglia, white matter abnormalities, and a chronic cerebrospinal fluid (CSF) lymphocytosis. Cree encephalitis shows phenotypic overlap with AGS although the conditions have been considered distinct because of immunological abnormalities observed in Cree encephalitis. We report that levels of interferon alpha (IFN-α), a marker of AGS, are raised in Cree encephalitis. Moreover, linkage analysis indicates that the disorders are allelic and refines the AGS1 locus to a 3.47 cM critical interval. Our data show that a CSF lymphocytosis is not necessary for the diagnosis of AGS and strongly suggest that AGS and pseudo-TORCH syndrome are the same disorder. Recognition of immunological dysfunction as part of the AGS phenotype provides further evidence of a primary pathogenic role for abnormal IFN-α production in AGS.